Flow Properties of Ficus Deltoidea Extract Powder and the Binders, Acdisol and Avicel. Issue 1 (7th January 2014) - Mohd Salleh, F.S.; Yusof, Y.A.; Anuar, M.S.; Chin, N.L.
Abstract This work aimed to investigate the flowability properties of the basic powders used to make tablets by means of direct compression. The main product in this study is Ficus deltoidea extract powder, while the excipients operated as binder were croscarmellose sodium (NaCMC or Acdisol) and microcrystalline cellulose (MCC or Avicel). Such excipient powders are essentially water insoluble and can also act as a filler, disintegrator and dissolver in tablet form. In order to compare and optimize powders regarding flowability, a Jenike shear tester was used to measure the flow properties of the powder particle, such as the effective angle of internal friction, flow function and the angle of wall friction. The experimental results showed higher flow property values for binders compared with F. deltoidea extract powder. These results provide essential information for the processing and handling of these powders during storage, transportation and also for the next processing step of powder – tabletting. Practical Applications F icus deltoidea is a popular herb in Malaysia and has become an international favorite for its health‐giving properties and nutritional benefits. This medicinal plant is locally known as Mas Cotek or serapat angin, telinga beruk and other few names. It is a valuable herbal plant that grows wild in the tropical forest of Malaysia, which has become an international favorite for its medicinal and healthy values. As a herbal tree, almost all of the parts of F. deltoidea plant including the roots, bark, stems, leaves and fruits are believed to have medicinal properties, which is useful for health purposes. Due to their promising and high commercial potential, the herb is studied to further develop their scientific usage in terms of pharmaceutical dosage (tablet). However, a small number of scientific work have been conducted to investigate the flow and physical properties of F. deltoidea. However, empirical knowledge and fundamental understanding of the relative contribution of flow properties of F. deltoidea extract powder to neutraceutical industries is lacking. Knowledge of flowabilities of this herb may improve its handling and processing and the quality of tablet production, particularly its mechanical properties.